Advances in Autism Spectrum Disorders and Intellectual Disability - Rizzo, Toni (MD Conference Express, 2014)
Advances in sequencing the entire human genome and large-scale genetic analyses have led to dramatically increased insights into neurodevelopmental disorders, including autism spectrum disorder (ASD) and intellectual disability (ID). Efforts are underway to use these insights to characterize the underlying molecular processes and functional pathways, with the goal of developing mechanism-based therapies for these disorders. This article provides an update on current approaches for the clinical and molecular genetic evaluation of individuals with ASD and ID, as well as discusses emerging treatments for neurodevelopmental disorders.